Effects of Change Capabilities and Knowledge Management on Financial Performance: The Case of Thai SMEs - Laksaniyanon, Benchamat (Journal of Public Administration, Public Affairs, and Management, 2021)
The small and medium enterprises (SMEs) of Thailand have played an important role for a long time as they are the fundamental of Thailand economy and like a mechanism sustainably developing the present economy of the country. This research aims to explain the effects of change capability and knowledge management affect financial performances of the small and medium enterprises in the processing and preserving of meat industry. The data was collected from the sample of 117 firms in 18 north-east provinces by using a mailed questionnaire method. The statistics was structure equation modeling (SEM). The results found that change capability and knowledge protect had significantly positive effects on financial performances of businesses, p<.05. For the knowledge transfer, the results found that it had no effect on financial performances of businesses, in the group of Thai small and medium enterprises.